Faktor yang Mempengaruhi Lama Waktu Pelaku SISKA untuk Memenuhi Kebutuhan Hijauan Pakan Ternak Sapi Di Provinsi Jambi: Faktor yang Mempengaruhi Lama Waktu Pelaku SISKA untuk Memenuhi Kebutuhan Hijauan Pakan Ternak Sapi Di Provinsi Jambi - Fatati, Fatati; Lubis, Adian Natama; Farhan, Muhammad; Novianti, Sri (Fakultas Peternakan Universitas Jambi, 2024)
Background: The existence of oil palm plantation crops in Jambi province allows for the development of an integration system of cattle with oil palm, known as SISKA (Oil Palm Cattle Integration System). which is contained in a national policy that is implemented in a regional policy in the form of a Regional Action Plan for Sustainable Oil Palm (RAD-KSB) for Jambi province in 2020-2024. SISKA development is carried out in the form of an area which in this case is represented by 3 of the 7-oil palms producing districts in Jambi province represented by the districts of Merangin (west), Batanghari (center) and West Tanjung Jabung (east). Fulfillment of cattle forage needs is done by browsing and grazing which is quite time consuming. Purpose: This study aims to determine the effect of the length of time SISKA actors to meet the forage needs of livestock feed in Jambi Province. Methods: This research was conducted in Batanghari district, Merangin district and Tanjung Jabung Barat district from March 06, 2023, to March 19, 2023. The method used was the survey method. Questionnaires were used to collect primary data on households sampled as respondents. The purposive sampling technique was used as a technique for determining respondents as samples, starting from the determination of districts, sub-districts, villages, and farmer households. The data in this study were analyzed by multiple regression analysis. Results: The results showed that there are three independent variables that significantly affect the length of time to meet the needs of animal feed forage, namely how to collect forage (X4), the distance to the source of forage (X5) and travel time to the source of forage (X6). Conclusion: The conclusion of this study is that the length of time for SISKA actors to meet the forage needs of cattle feed in Jambi province is determined by how to collect forage, distance to the forage source and travel time to the forage source.